Optic disc–fovea distance and myopia progression in school children: the Beijing Children Eye Study. Issue 5 (25th March 2018) - Guo, Yin; Liu, Li Juan; Tang, Ping; Feng, Yi; Wu, Min; Lv, Yan Yun; Xu, Liang; Jonas, Jost B.
Abstract: Purpose: To assess changes in the optic disc–fovea distance (DFD) with progressing myopia in school children. Methods: The school‐based, prospective, longitudinal study included grade‐1 children in 2011 who were yearly re‐examined until 2016. We measured DFD, optic disc diameters and width of parapapillary gamma zone (parapapillary region without Bruch's membrane (BM)) on fundus photographs. Results: Of 382 grade‐1 children examined in 2011, 294 (77.0%) children (mean age in 2011: 6.4 ± 0.5 years) returned to be examined in 2016. In relative terms, the increase in DFD (1.15 ± 0.33 mm) was more due to an increase in gamma zone width (+300% or 0.29 ± 0.30 mm) than an increase in macular BM length (+18% or 0.74 ± 0.21 mm). In multivariate regression analysis, longer increase in DFD was correlated (regression coefficient r 2  = 0.79) with longer axial elongation during the study period (p   <   0.001; standardized regression coefficient β : 0.61; non‐standardized regression coefficient B: 0.30; 95% confidence interval (CI): 0.26, 0.33), larger increase in gamma zone width (p   <   0.001; β : 0.35; B: 0.40; 95%CI: 0.32, 0.48) and longer axial length in 2011 (p   =   0.01; β :0.07; B:0.03; 95%CI:0.01, 0.06). Larger increase in gamma zone width was associated ( r 2  = 0.73) with larger increase in DFD (p   <   0.001; β : 0.51; B: 0.46; 95%CI: 0.39, 0.53), larger increase in the vertical‐to‐horizontal disc diameter ratio (p   <   0.001; β : 0.43; B:1.21; 95%CI: 1.00, 1.42) and longer vertical disc diameter (p   <   0.001; β : 0.15; B:0.24; 95%CI: 0.14, 0.34). Conclusion: In adolescent school children, axial elongation‐associated increase in DFD was mainly due to an enlargement (+300%) of parapapillary gamma zone, while macular BM length increased to minor degree (+18%). Gamma zone enlargement was correlated with axial elongation‐associated vertical optic disc rotation, potentially due to an increased backward pull of the optic nerve on the temporal optic disc border.